2019
DOI: 10.1021/acs.nanolett.8b04894
|View full text |Cite
|
Sign up to set email alerts
|

Hot Holes Assist Plasmonic Nanoelectrode Dissolution

Abstract: Strong light-absorbing properties allow plasmonic metal nanoparticles to serve as antennas for other catalysts to function as photocatalysts. To achieve plasmonic photocatalysis, the hot charge carriers created when light is absorbed must be harnessed before they decay through internal relaxation pathways. We demonstrate the role of photogenerated hot holes in the oxidative dissolution of individual gold nanorods with millisecond time resolution while tuning charge-carrier density and photon energy using snaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 52 publications
7
128
0
Order By: Relevance
“…47 Additionally, dissolution of AuNRs via substrate voltage tuning has been monitored using dark-field hyperspectral imaging. 48,54 Perhaps the most commonly reported reagent for etching single AuNRs in recent years is iron(III) chloride, starting with bulk studies in 2009. 82 Since then, FeCl 3 etching of single AuNRs has been reported using dark-field monitoring, sometimes utilizing Le Chatlier’s principle to drive the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Additionally, dissolution of AuNRs via substrate voltage tuning has been monitored using dark-field hyperspectral imaging. 48,54 Perhaps the most commonly reported reagent for etching single AuNRs in recent years is iron(III) chloride, starting with bulk studies in 2009. 82 Since then, FeCl 3 etching of single AuNRs has been reported using dark-field monitoring, sometimes utilizing Le Chatlier’s principle to drive the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of optical methods exist for probing nonluminescent single nanoparticles and molecules via photothermal, 3538 scattering, 3941 and other techniques. 4245 Observation of the chemical etching of single AuNRs has recently been accomplished with one-photon luminescence, 46,47 dark-field scattering, 4854 and liquid transmission electron microscopy (TEM). 55 However, a highly sensitive absorption technique for monitoring such chemical dynamics is needed to compliment these methods and would be extremely valuable for accessing targets that are not luminescent or are too small for scattering experiments.…”
mentioning
confidence: 99%
“…The reduced dimensions of the heteronanostructures minimize the probability of undergoing another relaxation/recombination process [68]. While the injection of hot electrons (using n-type semiconductors such as TiO 2 ) is the most accepted plasmon-driven charge transfer mechanism, there exist recent interesting studies claiming the importance of hot holes in other plasmonic-based systems [73,86,92,97,134,135,136,137] such as Au-NiO x , Au-pGaN [73], Au nanorods coated with a CoO nanoshell [138], Au nanostructures [101,139,140], or Ag-BiOCl hybrids [86,137].…”
Section: Discussionmentioning
confidence: 99%
“…This could be overcome by applying a bias. Landes and co-workers have found that the gold nanoparticles coated on an electrode could be dissolved at a bias of 0.48 V [134]. In this case, the chloride ions in the electrolyte solution can be adsorbed onto the gold surface.…”
Section: Metal Dissolutionmentioning
confidence: 99%